Augmented Reality and its Potential in Educating Primary School Students on Climate Change Awareness - Kifor Stefania; Lia Bologa; Diana Biclea; Olivia Andrei (Educaţia 21)
Augmented reality is an innovative way to enhance learning, transforming the way students access and assimilate knowledge. This technology has the potential to make education more accessible, attractive and effective. The purpose of this study is to identify the opinions of teachers / future teachers who teach / will teach at primary school, regarding the use of augmented reality applications in environmental education in primary school. Environmental issues in Romania, at all levels of education, are insufficiently explored, despite the growing need and efforts made by the Ministry of Education. Educational activities that contribute to preventing climate change, combating biodiversity loss, illegal deforestation, environmental pollution should be introduced from the earliest ages, and the ways of presentation should be as attractive, closer to the digital generation. Research data was collected via an online questionnaire with 24 questions, using the 5-point Likert scale. The sample consists of 133 participants selected by the non-probability sampling method. According to the survey results, most participants believe that the use of augmented reality applications has the potential to provide immersive and interactive experiences in environmental education classes for primary school students. However, the participants identified challenges and limitations that need to be considered before they can be fully accepted in the education sector. In conclusion, further research and development is needed to highlight the potential of augmented reality in primary school environmental education.